2021
DOI: 10.1007/s10533-021-00815-6
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of stream dissolved organic matter composition following glacier retreat in coastal watersheds of southeast Alaska

Abstract: Climate change is melting glaciers and altering watershed biogeochemistry across the globe, particularly in regions dominated by mountain glaciers, such as southeast Alaska. Glacier dominated watersheds exhibit distinct dissolved organic matter (DOM) characteristics compared to forested and vegetated watersheds.However, there is a paucity of information on how stream DOM composition changes as glaciers retreat and terrestrial ecosystem succession ensues. Importantly, it is unclear over what timescales these tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 91 publications
1
10
1
Order By: Relevance
“…Enriched water isotopes were associated with depleted DOM aromaticity and enhanced microbial activity, as reflected by the relationships with SUVA 254 and protein/humic (Figure ), which can be ascribed to lengthened ultraviolet exposure and retention time throughout the aquatic continuum. Specifically, the molecular formulae negatively correlated with water isotopes mainly belong to lignin and tannin described areas of van Krevelen space and overlapped with photolabile formulae previously observed in river samples. , Strong relationships between water isotopes and DOM composition have also been observed in other sparsely populated watersheds, such as within the Yukon River Basin, coastal southeast Alaska, , and deglaciated catchments in western Greenland . In these cases, different water isotopes can represent hydrologically isolated/connected lakes with distinct allochthonous input or catchment water sources (glacial versus nonglacial) from the perspective of different watershed types, confirming them being a promising proxy for inferring DOM sources and processing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Enriched water isotopes were associated with depleted DOM aromaticity and enhanced microbial activity, as reflected by the relationships with SUVA 254 and protein/humic (Figure ), which can be ascribed to lengthened ultraviolet exposure and retention time throughout the aquatic continuum. Specifically, the molecular formulae negatively correlated with water isotopes mainly belong to lignin and tannin described areas of van Krevelen space and overlapped with photolabile formulae previously observed in river samples. , Strong relationships between water isotopes and DOM composition have also been observed in other sparsely populated watersheds, such as within the Yukon River Basin, coastal southeast Alaska, , and deglaciated catchments in western Greenland . In these cases, different water isotopes can represent hydrologically isolated/connected lakes with distinct allochthonous input or catchment water sources (glacial versus nonglacial) from the perspective of different watershed types, confirming them being a promising proxy for inferring DOM sources and processing.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to precipitation input, some rivers and lakes in the Tibet region are seasonally directly fed by glacial meltwater, impacting the sources and processing of DOM in the downstream watershed. , Specifically, glacier melting has been considered the second most important reason for the expansion of lakes in the inner Tibetan Plateau apart from increased net precipitation . Previous studies highlight that glacier-derived DOM is chemically distinct from most aquatic systems and is typically aged, yet highly bioavailable, and is likely derived from atmospheric deposition and microbial processes in supraglacial or subglacial environments. ,,, It is reported that glacial DOM on the Tibetan Plateau is mainly composed of protein-like fluorophores and enriched aliphatic compounds. , Accordingly, the direct glacier-fed river samples had higher relative abundances of protein-like and aliphatic compounds than the other river samples (Figure ; Table S1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have characterized the composition of DOM pools at a range of detail spanning from bulk elemental carbon, nitrogen, and phosphorus ratios, using advanced mass spectrometry (i.e., Fourier transform ion cyclotron resonance mass spectrometry, or FT-ICR-MS) techniques (Repeta, 2015;McCallister et al, 2018). In particular, FT-ICR-MS, which can resolve hundreds to thousands of individual molecular formulae from a single sample (McCallister et al, 2018), has been increasingly applied over the past decade to uncover the diversity of molecules present in the DOM pool (Kellerman et al, 2018;Cooper et al, 2020;Holt et al, 2021). This technique has clear limitations as it cannot capture the whole DOM pool as commonly used extraction methods such as solid phase are chemically selective (Chen et al, 2016;Baltar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Glacial meltwater is highly influential to downstream ecosystems by creating a unique habitat template ( Uehlinger et al, 2010 ), exporting nutrients and organic matter (e.g., Hood et al, 2009 ; Singer et al, 2012 ; Hawkings et al, 2015 ; Kohler et al, 2017 ; Irvine-Fynn et al, 2021 ), and dispersing microbial life ( Wilhelm et al, 2013 ; Cameron et al, 2017a ; Hotaling et al, 2019 ; Kohler et al, 2020b ; Ezzat et al, 2022 ). At the same time, glaciers are retreating around the world at unprecedented rates ( IPCC, 2019 ), altering their relative importance as a water source in catchments as the balance of water coming from non-glacial sources, including groundwater and precipitation, changes ( Milner et al, 2017 ; Holt et al, 2021 ). As a result, sources and relative quantities of solutes, particulates, and microbial cells from within catchments are likely to shift with glacier shrinkage, potentially impacting downstream ecosystems.…”
Section: Introductionmentioning
confidence: 99%